2020
DOI: 10.3389/fonc.2020.570981
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Activated Regional Lymph Nodes Predict Favorable Survival in Early-Stage Triple-Negative Breast Cancer

Abstract: Immune response and immunotherapy play important roles in triple-negative breast cancer (TNBC). However, it is difficult to judge whether cancer is “immune-inactivated” or “immune-activated” by the carcinoma itself. The immune reaction of the microenvironment or the host to the tumor might be more informative. We assumed that clinically enlarged but pathologically negative regional lymph nodes served as an indicator for early immune response to tumors. First, we identified women with pN0 breast cancer disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…However, the definition of "PD-L1-positive" population in clinical practice remains challenging (69). In addition, assessing whether a cancer is "immune activated" or "immune inactivated" is difficult (70). Therefore, finding new molecular biomarkers for the prediction immunotherapy response for TNBC is an urgent issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the definition of "PD-L1-positive" population in clinical practice remains challenging (69). In addition, assessing whether a cancer is "immune activated" or "immune inactivated" is difficult (70). Therefore, finding new molecular biomarkers for the prediction immunotherapy response for TNBC is an urgent issue.…”
Section: Discussionmentioning
confidence: 99%
“…TNBC is the subtype of BCs most related to TIL infiltration and PD-1/PD-L1 expression (70). Among the TNBC subtypes, BLIA is enriched in immune-response genes, immune activated, and can benefit the most from immune checkpoint inhibitor treatment (69).…”
Section: Discussionmentioning
confidence: 99%
“…compared the outcomes of patients with cN0 and cN1 in preoperative assessment among 692 pN0 cases, and BCSS of cN1 patients was unexpectedly significantly longer than cN0 ones in TNBC. Using RNA sequencing, they found that enlarged ALNs in clinical imaging had higher expression of immune-related genes, such as IL21 , CCL17 , AOC1 , APOC2 , and NCCRP1 , and more abundant immune cells, such as dendritic cells, CD4+ T cells, and CD8+ T cells ( 36 ). Increased anti-tumor immunity improved survival, which partly explained our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Increased numbers of T and B cells in sentinel LNs [ 52 ] have been associated with longer DFS across different breast cancer subtypes irrespective of their nodal status, as are increased levels of axillary node CD4+ T cells and DC populations in LN-positive breast cancer patients [ 44 , 52 ]. Patients with enlarged LNs without metastatic involvement (indicative of an active immune response) experience longer breast-cancer-specific-survival [ 56 ]. Topically, swollen LNs are an unanticipated side effect of the immune reaction engendered by the COVID-19 vaccine which has been complicating breast cancer screenings.…”
Section: Lymph Nodes: the Immune Capital Of Anti-tumour Responses In ...mentioning
confidence: 99%